Frequency of Hepatitis B Virus carrier by Detecting AntiHBc Antibody among HBsAg Negative Blood Donors - Islam, Kashfia; Hoque, Mazharul; Nahar, Samsun; Md. Taimur, Syed Dawood; Rahman, Zeenat Farzana; Sultana, Nahid (Bangladesh Journal of Medical Science, 2016)
Background & Objective: Transfusion associated hepatitis B virus (TAHBV) infection continues to be a major problem despite mandatory screening for hepatitis B surface antigen (HBsAg). This is because HBsAg is not detected during the window period of the infection. This study was designed to assess the frequency of anti HBc antibody among HBsAg negative donor and also to determine the demographic profile of healthy blood donors. Material & Method: This cross sectional observational study was carried out in the Department of Transfusion Medicine, BSMMU, Dhaka during the period of May 2014 to April 2015. A total number of 100 consecutive healthy blood donors who were clinically and physically healthy and serologically found to be free from HBsAg, HCV and HIV by rapid chromographic test were included in this study. Results: Within the 100 patients among them history of jaundice was found in 17(17.0%). There all (100.0%) subjects had negative HBsAg and 14(14.0%) subjects had positive anti HBc-Ab. Anti HBc-Ab was statistically significant (p<0.001) in Z-test. Conclusion: This study was undertaken to assess the prevalence of anti HBc antibody among healthy blood donors with HBsAg negative in rapid chromatography method. The prevalence of anti HBc antibody was about 14 (14.0%) among 100 HBsAg negative blood donors. History of blood donation was found in almost two third 65 (65.0%). So, anti HBc antibody screening is an useful tool for estimating the risk of transfusion transmitted HBV infection. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.66-69